A Philosophical Critique Of The Problem Associated With Euthanasia - Abakare, Chris O. (Program Studi Sosiologi, 2020)
The patient's life in adverse conditions is considered as a life supported by a machine. During these conditions what is the value of life? If the patient has given a living will stating that under certain circumstances he/she prefers peace rather than continuing life with the artificial life support machines, and the choice of the individual is made in a stable and rational mind, such position is always considered by authority while deciding adverse situations. However, there are situations where the patient is under stress or not in his stable mind, in taking decisions about his last wish and when the actual consent of the patient is unavailable to authorities. The decision that ought to be taken under these conditions on behalf of the patient falls on the parents, relatives, doctors and society. The ethical dilemmas involved in the physician's perspective forms the crux of this work. Medical professional rules include the duties of the society, physician and patient. But this work deals with the rightness and wrongness of the application of euthanasia from the perspectives of physicians and their duties.